The Reconstruction of Female Images in the English Translations of Shui Hu Zhuan - Zichen Zhao (Comparative Literature: East & West)
Shui Hu Zhuan, a classical Chinese novel, depicts an uprising led by Song Jiang that took place in the late Northern Song Dynasty (960–1127). Characteristically, most women in Shui Hu Zhuan are portrayed negatively, showing a misogynistic tendency. This study aims to examine the female images in the four full English translations of Shui Hu Zhuan to explore how the translators reconstructed the negative portrayal of women by the original narrator with the theoretical guidance of feminist translation theory and strategies. The translators of the four translations are from different socio-cultural backgrounds and serve different publishers and publishing purposes; therefore, these socio-cultural factors influencing their reconstructions of female images are also discussed in this study.